LEARNING E-COMMERCE - Moʻminova Kanizaxon Yoʻldashali qizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This study aims to analyze the impact of e-commerce on various aspects of business operations and consumer behavior. It explores the growth and development of online retail platforms, examining their advantages and challenges. The study investigates the factors influencing consumers’ decision-making processes in online shopping, including trust, convenience, and product variety. It also examines the strategies employed by businesses to enhance customer experience and increase sales in the e-commerce landscape. Furthermore, the study evaluates the economic and social implications of e-commerce, including its effects on employment, market competition, and sustainability. Overall, this research provides valuable insights into the dynamic nature of e-commerce and its significance in contemporary business practices.